THE PLEISTOCENE BATHYAL TELEOSTEAN FAUNA OF ARCHI (SOUTHERN ITALY): PALAEOECOLOGICAL AND PALAEOBIOGEOGRAPHIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The early-middle Pleistocene teleostean fauna of the Archi section, cropping out along the Calabrian side of the Messina Straits was studied.  The integrated approach, based on the palaeobathymetric method coupled with the palaeoecological approach, already used on deep circalittoral and epibathyal assemblages, was applied for the palaeoenvironmental reconstruction.  The otholith benthic and benthopelagic associations, strongly bathyal in their composition, suggest a deep bathyal palaeoenvironment, 500 to 1000 m deep, which is in agreement with the invertebrate benthic faunas. Compositional, structural, and taxonomic features of the teleostean assemblages indicate clearly Atlantic or more generally oceanic affinities.  The Archi teleostean fauna indicates a palaeoceanographic pattern with deep-water and near-bottom temperature lower than 8-10°C, quite different from the Recent mediterranean.